A 55 CENTS CIGARETTE TAX INCREASE WILL HARM NEW YORK RETAILERS (Tufts Archival Research Center, 2007)
Report on the economic impact of a cigarette tax increase on New York retailers. Predicts that such an increase would lead to a steep increase in cigarette taxes nation wide. Anticipates cross border sales, increased sales on Indian reservations, and cigarette smuggling. Discusses commercial losses, convenience store losses, and the regressivity of such taxes.